THE BENEFICIAL EFFECTS OF PROPOLIS ON OSTEOBLAST DIFFERENTIATION: A LITERATURE REVIEW - Jessy Wijaya; Rezmelia Sari; Suryono (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Optimal bone regeneration is contingent upon the activities of osteoblasts, which are modulated by signalling molecules. Propolis, an abundantly beneficial natural substance, has the potential to induce the release of signalling molecules. Review: Four essential elements required for tissue regeneration via tissue engineering: scaffolds, signalling molecules, stem cells, and vascularization. Subsequently, osteoblast differentiation and activity are enhanced by signalling molecules induced by propolis. Propolis contains active ingredients that influence every stage of osteoblast differentiation. Propolis-induced increases in the release of signalling molecules (BMP, FGF, TGF) and the transcription factor RUNX2 stimulate the expression of diverse osteoblastogenic markers at each stage of differentiation: type I alpha 1 collagen during proliferation, alkaline phosphatase during maturation, and osteocalcin during mineralization. Conclusion: Propolis has the capacity to promote bone regeneration through its involvement in all phases of osteoblast differentiation (inducing the release of signalling molecules, increasing the transcription factor, and increasing the expression of osteoblastogenic markers). Additional research is required to determine how propolis influences the equilibrium between osteoblast and osteoclast activities in order to maintain optimal bone homeostasis and remodelling. The prolonged duration of bone regeneration necessitates the use of a carrier for propolis to remain on bone defects for an extended period of time.